Designable yolk-shell nanoparticle@MOF petalous heterostructures - Liu, Yayuan (2014)
Controlled integration of nanoparticles (NPs) and metal-organic frameworks (MOFs) is crucial for expanding the applications of MOFs-based materials. In this study, the facile encapsulation of pre-synthesized NPs into carboxylic acid-based MOFs using NPs@metal oxide core-shell nanostructures as the self-template is demonstrated. The shell dissolved gradually in the mildly acidic growth solution created due to the dissociation of the ligands and thus, directing the growth of the MOFs crystals by providing metal ions. With the protection of the metal oxide shell, various NPs (Au NPs, Au nanorods, Pd nanocubes, Pt-on-Au dendritic NPs) could be encapsulated easily without being aggregated or dissolved in the reaction mixture. Importantly, instead of forming the exact replicate of the self-template, the obtained NP@MOF heterostructures exhibited a yolk-shell morphology with a central cavity and a certain degree of mesoporosity. The formation of the well-defined yolk-shell structure was demonstrated to be dependent on both the choice of the solvent and the dissolution behavior of the metal oxide shell. Finally, the obtained heterostructures were employed for heterogeneous catalysis, in which the size-selectivity of the MOFs shell was perfectly retained.